Banalitas Salib: Kajian Teologi Biblika 1 Korintus 1:18-25 dan Relevansinya dalam Khotbah Modern dan Pelayanan Kontemporer - Elkria Juanta; Wenda Maraja; Van Heifel Radon Ambuliling (Vieka Wahana Semesta, 2026)
This study is motivated by the phenomenon of a theological crisis within the Indonesian church ecosystem, particularly the trivialization of the cross, where the pulpit often reduces the essence of suffering to mere rhetorical embellishment and a prosperity theology that is purely anthropocentric. The primary objective of this study is to uncover the original exegetical meaning of the text 1 Corinthians 1:18–25, construct a comprehensive biblical theology regarding the doctrine of the cross, and develop a contemporary restorative homiletic paradigm. This study employs a qualitative method through a triadic integrative approach, namely historical-grammatical exegesis, biblical theology of the history of redemption, and the empirical analytical framework of the four tasks of practical theology. The main findings of the study demonstrate that the message of the cross is a radical antithesis to worldly wisdom, functioning as an eschatological demarcation sword that shatters the arrogance of human rationality. The findings indicate that pastors and church councils must absolutely deconstruct managerial pragmatism and return to the expository homiletic model in order to restore spiritual depth, the integrity of ministry, and its prophetic relevance in the current era of digital advancement.